Influência da adição de dextrina de trigo sobre características reológicas da massa e qualidade de biscoitos - Mansur, Christian Soares (2011)
Wheat dextrin act as a soluble dietary fiber, promoting regulation of gastrointestinal tract, stabilization of insulin and blood glucose levels, as well as regulation of serum lipids. The aim of this experimental work was to evaluate the influence of wheat dextrin addition on rheological characteristics of the wheat dough and on technology and nutritional biscuit quality. The effect of replacing part of the wheat flour (0, 5, 10 and 15%) by wheat dextrin on the rheological characteristics of the dough was investigated using farinograph and extensograph measurements. Three commercial wheat flours ranked as weak, intermediate and strong were used for this purpose. Dough stability increased upon addition of wheat dextrin, except for wheat flours such as intermediate and strong containing 15% of dextrin. At all level of replacement of dextrin by wheat flour, significant decrease in water absorption was observed for all wheat flours tested. Weak and strong wheat dough with 5% of dextrin has not influence on ratio R/E. Up to certain levels, wheat flour could be replaced by wheat dextrin without compromise the dough consistency. A short-dough biscuit recipe with different levels of wheat flour replacement (0, 7, 14 and 21%) by wheat dextrin was tested. Physical, mechanical, sensory and nutritional characteristics of the biscuits were evaluated. Sensory attributes such as crispness was improved with 7% of dextrin, flavor and global acceptance have higher rates with 21%, comparing to biscuits without dextrin. The general acceptance was better to the enriched fiber biscuit. The thickness, specific volume and spread of the biscuits were not negatively affected due to dextrin. There was significant increase in the width of the biscuits with 21% of wheat dextrin. Water activity and moisture content showed augment with addition of 14 and 21% of dextrin. Addition of wheat dextrin to biscuit promoted a yellowness color. Crispness perception of the biscuits with wheat dextrin was better than the common biscuit, both under compression and shear forces. Fiber analysis showed a significant increas e of soluble fiber values until 12.28% to the read-to-eat biscuits.Protein content of the biscuits showed values between 11.83 and 13.17%. Addition of wheat dextrin into biscuits formulation could be useful to adjust rheological parameters of dough towards target values. Addition of 21% of dextrin to biscuit showed acceptable properties, as well as higher soluble fiber content with lesser effect on sensorial neither physical properties of biscuit, which could causes rejection by consumers.